D-optimal mixture design for optimization of topical dapsone niosomes: in vitro characterization and in vivo activity against Cutibacterium acnes - Basant A. Habib; Nourtan F. Abdeltawab; Ibtehal Salah Ad-Din (Taylor & Francis Group, 2022)
This study aimed to illustrate the use of D-optimal mixture design (DOMD) for optimization of an enhancer containing Dapsone niosomal formula for acne topical treatment. Mixture components (MixCs) studied were: Span 20, Cholesterol, and Cremophor RH. Different responses were measured. Optimized formula (OF) was selected to minimize particle size and maximize absolute zeta potential and entrapment efficiency. Optimized formula gel (OF-gel) was prepared and characterized. OF-gel in vivo skin penetration using confocal laser scanning microscopy and activity against Cutibacterium acnes in acne mouse model were studied. Based on DOMD results analysis, adequate models were derived. Piepel and contour plots were plotted accordingly to explain how alteration in MixCs L-pseudo values affected studied responses and regions for different responses' values. The OF had suitable predicted responses which were in good correlation with the actually measured ones. The OF-gel showed suitable characterization and in vivo skin penetration up to the dermis layer. In vivo acne mouse-model showed that OF-gel-treated group (OF-gel-T-gp) had significantly better recovery (healing) criteria than untreated (UT-gp) and Aknemycin®-treated (A-T-gp) groups. This was evident in significantly higher reduction of inflammation percent observed in OF-gel-T-gp than both UT-gp and A-T-gp. Better healing in OF-gel-T-gp compared with other groups was also verified by histopathological examination. Moreover, OF-gel-T-gp and A-T-gp bacterial loads were non-significantly different from each other but significantly lower than UT-gp. Thus, DOMD was an adequate statistical tool for optimization of an appropriate enhancer containing Dapsone niosomal formula that proved to be promising for topical treatment of acne.